Embraced Wood: Circular construction method for composite long-span beams from unprocessed reclaimed timber, fibers and clay - Asa, Pelin; El Feghali, Christelle; Steixner, Christian; Tahouni, Yasaman; Wagner, Hans Jakob; Knippers, Jan; Menges, Achim (Construction & building materials, 2024)
This paper presents a method to expand the availability of wood in construction by establishing a computational design and robotic fabrication workflow. Digital tools enable the evaluation of the structural, material and geometric properties of pieces of unknown origin to create beams from unprocessed reclaimed timber using clay and natural fibers. Methods to overcome challenges such as material irregularities, embedded fasteners, size variation, and surface toxins allow for timber that would otherwise only be downcycled to serve a structural high-value use. A full-scale prototype beam was fabricated to test the fabrication process, and structural testing was conducted to demonstrate design specific span and loading performance. •A workflow for building laminated beams from unprocessed reclaimed timber elements.•Use of computational design addresses the irregularities of reclaimed materials.•Use of clay and natural fibers as binding material creates a disassemblable system.•Clay encapsulation mitigates emission of toxic substances in the coatings.•An end effector design and fabrication process for fiber wrapping are demonstrated.